Pengembangan Buku Panduan Intervensi Bagi Orang Tua Dengan Anak Autis Non Verbal di SLB Negeri I Gowa - Tatiana Meidina; Bastiana Bastiana; St. Kasmawati (Seminar Nasional LP2M UNM, 2022)
Abstrak. This study aims to develop a communication intervention guidebook for parents with non-verbal autistic children and is a Research and Development (R&D) type research with the ADDIE research and development model, which has 5 steps. Data collection techniques in this study used interview techniques and questionnaires. Data analysis techniques are descriptive qualitative and descriptive quantitative. The results obtained in this study are; the level of need for guidebooks is obtained from the analysis stage; The feasibility test on the initial draft of the guidebook was obtained. The validity test was carried out by 2 teachers who taught non-verbal autistic children on the material and media of the guidebook using the Gregory formula with very valid validity results and continued to the product revision stage; and the legibility test stage using the content validity test of the Aiken V formula with very valid validity results and the final product is the production of a communication intervention manual for parents with non-verbal autistic children. Kata Kunci: Intervention, Communication, Non-Verbal Autism